(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article describes the achievements of music in our country in the post-independence years and the impact of music on the education of children, adolescents and young people, developing methods with the help of musical tones and classical music in the education and upbringing of young people.